2004
DOI: 10.1103/physreve.69.046610
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the Green’s function from the correlation of coda waves: A derivation based on stationary phase

Abstract: The Green's function of waves that propagate between two receivers can be found by cross-correlating multiply scattered waves recorded at these receivers. This technique obviates the need for a source at one of these locations, and is therefore called "passive imaging." This principle has been explained by assuming that the normal modes of the system are uncorrelated and that all carry the same amount of energy (equipartitioning). Here I present an alternative derivation of passive imaging of the ballistic wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
965
0
16

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,069 publications
(995 citation statements)
references
References 20 publications
14
965
0
16
Order By: Relevance
“…Not all source locations are equally important and practical configurations with open boundaries may result in accurate results, because the main contributions come from sources located at stationary points [9]. The presence of weak losses has no effects on the phase of the extracted Green's function, while some amplitude errors but no spurious events occur [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all source locations are equally important and practical configurations with open boundaries may result in accurate results, because the main contributions come from sources located at stationary points [9]. The presence of weak losses has no effects on the phase of the extracted Green's function, while some amplitude errors but no spurious events occur [17].…”
Section: Discussionmentioning
confidence: 99%
“…where the contrast function ∆M is the same as in Equation (9). No assumptions about the material matrixM has been made, other than that its adjoint exists.…”
Section: Green's Function Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…Using correlational forms of the reciprocity theorems, Wapenaar & Fokemma (2006) showed how inter-receiver Green's functions could be constructed by crosscorrelating recorded fields whereas other studies have also revealed the limitations of that method (Snieder 2004;Roux et al 2005;Gouédard et al 2008). For obtaining a diffuse field Halliday & Curtis (2008) analyse the requirements in terms of source distribution for the retrieval of scattered surface waves.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the randomness of the coda results from multiple scattering by randomly distributed scatterers, the fact that seismic noise is assumed to be random is mostly because of the distribution of sources at the surface of the Earth (e.g. Derode et al 2003;van Tiggelen 2003;Malcolm et al 2004;Snieder 2004). …”
Section: Introductionmentioning
confidence: 99%